THE INTEGRATION BETWEEN NEUROPEDAGOGY AND CREATIVITY IN HIGHER EDUCATION - Kilicheva Karamat (American Journals Publishing, 2024)
Neuroscience and neurodidactics, and thus neuropedagogy, are playing an increasingly important role every day in academic institutions seeking to optimize their educational processes. Creativity is a person’s ability to generate ideas, find innovative solutions to problems, and create something new and original. Creative inviduals are able to notice unexpected connections between phenomena and objects and go beyond standard thinking. To do this, it is needed to use logic and imagination at the same time - that is, analyze the problem and think outside the box. Therefore, this paper aims to review past research studies to analyze the integration of neuropedagogy and creative approach in education.
Keywords: Neuropedagogy, neuroscience, education, creativity, creative education